Features of formation and functioning of phytoplankton of small reservoirs - Shelyuk, Yu.S. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2022)
Regularities of phytoplankton formation and functioning of small reservoirs are established. Chlorophyta (32.7% of the total list of species) and Bacillariophyta (24.6%) were found to be predominant in species richness. Cyanobacteria species have been found to increase as the area and volume of reservoirs increase, and Euglenozoa is ahead of them in smaller bodies of water. The main abiotic parameters that determine the changes in the structural parameters of phytoplankton of the studied reservoirs are determined. The main differences in the structural and functional characteristics of phytoplankton of small reservoirs built on Polissya rivers in comparison with large Dnieper and Volga ones have been clarified.